The Photographer as Producer: Technique and Dialectics in Berenice Abbott and Elizabeth McCausland’s Changing New York - Periáñez Llorente, Luis (Escritura e Imagen, 2023)
This paper recomposes the theoretical framework deployed by Walter Benjamin in The Author as Producer and in The Work of Art in the Age of its Technical Reproducibility to interpret from there the aesthetic specificity and political potential of the original project by Berenice Abbott and Elizabeth McCausland, Changing New York. In the same way, said framework will serve to analyze the consequences of the censorship suffered by the project in its editing process.
Keywords: Benjamin; Abbott; McCausland; Changing New York